Need Analysis for the Development of Electronic Students' Worksheet (E-LKPD) on Education Sustainable Development on the Use of Eco Enzyme - Erni Trayati; Erna Retna Safitri; Triyanto Triyanto (Akademika, 2024)
The concept of continuous education, technology integration, and increasing environmental awareness is a good synergy in learning. Continuing education is a holistic approach. The teaching materials developed not only focus on the use of eco enzymes, but also relate them to broader sustainability issues. The purpose of this study is to describe the analysis of the need for the development of digital teaching materials based on Education Sustainable Development on the use of eco enzymes This type of research is research and development (R&D) research. The instrument used in this study was in the form of a questionnaire to analyze the needs of teachers and students of SDN 19 Lahat. Based on the results of the research conducted, it can be concluded that teachers expressed their desire to develop digital teaching materials based on education sustainable development in the form of E-LKPD on the use of eco enzymes. In addition, the results of the questionnaire on student perception showed a score of 75. Students consider that the learning methods used so far have not been able to make a good understanding of the material presented so that the development of digital-based teaching materials in the form of e-LKPD can be a solution to the problems that have occurred in learning so far